Combined fractional anisotropy and subcortical volumetric deficits in patients with mild-to-moderate depression: Evidence from the treatment of antidepressant traditional Chinese medicine - Li, Yuan; Wang, Junjie; Yan, Xu; Li, Hong (Frontiers in Neuroscience, 2022)
Numerous neuroimaging studies have demonstrated that diverse brain structural plasticity could occur in a human brain during a depressive episode. However, there is a lack of knowledge regarding the underlying mechanisms of mild to moderate depression (MMD), especially the changes of brain structural characteristics after treatment with Shuganjieyu capsule (SG), a kind of traditional Chinese medicine which has been recommended for the specialized treatment of MMD. In this study, we investigated the structural brain plasticity in MMD that have been undergoing eight weeks SG treatment compared with age- and sex-matched healthy controls (HCs) and assessed the relationship between these brain structural alternations and clinical symptoms in MMD. At the baseline, we found that: (1) fractional anisotropy (FA) values in MMD patients were found to be significantly increased in the regions of anterior limb of internal capsule (ALIC) (MNI coordinates: Peak(x/y/z) = 102,126,77; MMD FApeak(Mean±SD) = 0.621±0.043; HCs FApeak(Mean±SD) = 0.524±0.052; MMD > HCs, t = 9.625, p < 0.001) and posterior limb of internal capsule (PLIC) (MNI coordinates: Peak(x/y/z) = 109,117,87; MMD FApeak(Mean±SD) = 0.694±0.042; HCs FApeak(Mean±SD) = 0.581±0.041; MMD > HCs, t = 12.90, p < 0.001), and FA values were significantly positively correlated with HAMD scores in MMD patients; (2) MMD patients showed smaller gray matter volume (GMV) of the dorsolateral prefrontal cortex (DLPFC), frontal cortex, occipital cortex, and precuneus, and the GMV of DLPFC was negatively correlated with HAMD scores. After SG treatment, we found that: (1) the HAMD scores decreased; (2) FA values were significantly decreased in the regions of the ALIC and PLIC compared to those at baseline and TBSS revealed no significant differences in FA values between MMD patients and HCs; (3) the structural characteristics of DLPFC in MMD patients obtained at the eighth week were improved; e.g., no significant differences in GMV of DLPFC between the two groups. Taken together, our results provided neuroimaging evidence suggesting that SG is an effective treatment for MMD patients. Moreover, alterations of GMV after eight weeks of SG treatment indicated a potential modulation mechanism in brain structural plasticity within the DLPFC in MMD patients.